Measurement of Neutral Mesons in p-Pb collisions at √sNN = 8.16TeV with the ALICE detector - Ahmed, Samah (Department of Physics, 2020)
The measured transverse momentum spectra of neutral pion π 0 and η mesons are presented for p-Pb collisions at √ sNN = 8.16 TeV using the photon conversion method for the signal extraction. This method uses the tracking and particle identification capabilities of the central barrel detectors of ALICE. Signal extracted down to 0.3 GeV/c and 0.7 GeV/c for π 0 and η respectively. The resulting spectra are presented and systematic uncertainties have been evaluated. A suppression of the yield compared to pp collisions at the same center of mass energy is observed in RpA for both mesons. Comparisons to theory predictions show consistency with the spectra and RpA.